Invisible, successful, and divided Vietnamese in Germany since the late 1970s - Frank Bösch; Phi Hong Su (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Until the 1970s, only 1000 Vietnamese lived in West and East Germany, most of them international students. West Germany, in particular, had not yet been confronted with non-European refugees. This changed after 1978 with the influx of around 35,000 "boat people" from Viet Nam and other countries in South East Asia, who arrived as part of a contingent quota admission. Their entry led to new strategies for integration, including obligatory language classes and a host of measures resembling those in other countries of refugee resettlement. Yet, the German case differs from other countries because of the simultaneous arrival of non-refugee Vietnamese, who came on temporary labour contracts to socialist East Germany starting in 1980. These two migration streams would converge when Germany reunified in 1990. Drawing on mixed qualitative methods, this paper offers a strategic case for understanding factors that shaped the arrival and resettlement experiences of Vietnamese refugees and contract workers in Germany. By comparing two migration streams from the same country of origin that experienced varied contexts of reception (government, labour market, and ethnic community), we suggest that a context of reception need not be uniformly positive for immigrants and refugees to have an integration experience deemed successful.
Keywords: J15; O15; R23; N34; N94; 330; integration; international migration; refugees; Germany; media analysis; qualitative interviews